The skillful teacher : on technique, trust, and responsiveness in the classroom - Brookfield, Stephen (San Francisco, CA : Jossey-Bass, 2015)
"Energize your classrooms with these key techniques for college teachingStudents say the best teachers get them excited about learning, stretch their thinking, and keep them actively involved in class. But with increasingly diverse classrooms and constantly changing technology, each semester throws up new challenges for engaging students.Discover how to keep your teaching, and your students, energized with The Skillful Teacher, a practical guide to effective techniques, approaches, and methods for today's college classrooms. Providing insights, reflections, and advice from his four decades of college teaching, Stephen Brookfield now adapts his successful methods to teaching online, working with diverse student populations, and making classrooms truly inclusive. As well as being completely revised, updated, and rewritten, this edition adds six brand new chapters on: Teaching critical thinking Using play and creativity in the classroom Teaching in teams Helping students take responsibility for learning Teaching about racism Exercising teacher power responsibly Readers will delve into what learning feels like from a student's perspective, as well as absorb the wisdom of veteran college faculty with whom the author has worked. Themes from the bestselling previous editions remain, but are revisited and expanded with the perspective of an additional decade in the classroom. This authoritative guide is now even more comprehensive to better serve teachers looking to improve. Whether you are new to the classroom or are looking to rise to new challenges, The Skillful Teacher will provide answers, expand your repertoire of techniques, and invigorate your teaching and your classrooms"--
Machine generated contents note: Preface v--xv Acknowledgments About the Author ii--iv 1 Experiencing Teaching 1--16 2 The Core Assumptions of Skillful Teaching 17--32 3 Understanding Our Classrooms 33--48 4 What Students Value in Teachers 49--64 5 Understanding and Responding to the Emotions of Learning 65--81 6 Lecturing Creatively 82--98 7 Using Discussion Methods 99--116 8 Teaching in Diverse Classrooms 117--132 9 Teaching About Racism 133--148 10 Using Play and Creativity 149--168 11 Teaching in Teams 169--184 12 Teaching Students to Think Critically 185--200 13 Teaching Online 201--218 14 Giving Helpful Evaluations 219--235 15 Helping Students Take Responsibility for Learning 236--251 16 Understanding Students' Resistance to Learning 252--267 17 Responding to Students' Resistance to Learning 268--283 18 Exercising Teacher Power Responsibly 284--299 19 Negotiating the Politics of Teaching 300--315 20 Staying Sane: 16 Maxims of Skillful Teaching 316--331 References 332--362 Index .
Includes bibliographical references and index.
LTIC
Book Finder Intentional
Keywords: College teaching; EDUCATION / Teaching Methods & Materials / General; EDUCATION / Higher